Legal knowledge and information systems : JURIX 2009, the twenty-second annual conference - Governatori, Guido (Frontiers in artificial intelligence and applications ;, 2009)
The 22nd edition of the JURIX conference was held in Rotterdam on the 17th and 18th December and was hosted by the Erasmus University Rotterdam. While the conference was back to its country of origin, JURIX continues to attract a wide international audience. This year, the conference received submissions from all five continents. This clearly demonstrates the lively and growing interest for the highly interdisciplinary discipline of legal informatics. The selection of papers for this edition of JURIX covers a wide variety of topics in legal informatics, including contributions on established f.